Analyzing the Effects of Platform Reliability, Response Time, Safety Features, and User Experiences, on Customer Loyalty in Industrial Online Transportation Service in Indonesia - Prananta, Arie Wahyu; Afifudin, Moch; Taufikur Rahman, Rahmat; Bahar, Anisa (International Journal of Business, Law, and Education, 2024)
This study investigates the effects of platform reliability, response time, safety features, and user experience on customer loyalty within the industrial online transportation services in Indonesia. Utilizing a quantitative approach, data were collected from a sample of users through structured questionnaires. The results revealed significant positive relationships between all examined factors and customer loyalty, with safety features and user experience being the most influential. The findings emphasize the importance of reliable platforms, timely service, robust safety measures, and positive user experiences in enhancing customer retention. These insights provide practical implications for companies in the online transportation sector to develop strategies that foster customer loyalty and maintain a competitive advantage.